ANALISIS PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN YANG DIMEDIASI OLEH KEPUASAN PELANGGAN (Studi Pada Perumda Air Minum Tirta Moedal Kota Semarang) - Dyah Ramadhanty (Jurnal Akuntansi dan Pajak, 2023)
The purpose of this study was to examine the effect of service quality and product quality on customer loyalty mediated by customer satisfaction. This research is based on a research gap so that further research is still needed. The population of this study is all customers of the Tirta Moedal Regional Drinking Water Company (PDAM), totaling 180,520 customers as of March 2022. The method of taking respondents uses non-probability sampling with a purposive sampling technique. The research data is in the form of primary data and secondary data. Methods of data collection using questionnaire techniques, interviews and observation. The data analysis technique used in this study is the SEM (Structural Equation Model) method with the help of the Analysis of Moment Structures (AMOS) program. Based on the results of the analysis that has been carried out, the results show that service quality has a positive and significant effect on customer satisfaction, product quality has a positive and significant effect on customer satisfaction, service quality has a positive and significant effect on customer loyalty, product quality has no significant effect on customer loyalty, and satisfaction customers have a positive and significant effect on customer loyalty. The research results are expected to answer the problems formulated in this study. Keywords: service quality; product quality; customer loyalty; customer satisfaction